Reactividad del fenol en soluciones acuosas de nitrito de sodio en presencia de micelas de sulfato de dodecilo de sodio - Squadrito, Giuseppe (1991)
The rcactivity of phenol in aqueous solutions containing sodium ni tri te in the prescncc of sodium dodecylsulfate micellcs has bccn studied. Thc reaction yields ortho- and para-nitrophenol, para-nitrosophenol and 2,4-dinitrophenol at low convertions, in yiclds that depend on the pH. The rcsults ha ve been rationalized in terms of a reaction mechanism that involves free radicals.